Investigation Of The Levels Of Feeding Feelings, Emotional Eating And Perfectionism Of University Students Who Do Sports And Do Not Do Sports - ÇAĞLAYAN TUNÇ, Aygül (Progress in Nutrition, 2021)
Aim: The aim of the study is to examine the emotional eating, nutritional feelings and perfectionism levels of university students who do sports and those who don't. Material and Method:  260 people selected by simple random sampling from university students participated in the study. The research is designed according to the relational screening model. In data collection; personal information form, Nutrition Emotions: Emotional Eating and (APS) Perfectionism Scale were used. The analysis of the data was made with the SPSS program and the normal distribution values for the test types to be used were analyzed. Skewness and Kurtosis values showed normal distribution. Independent sample t test was used for paired comparisons and Anova test was used for more than two comparisons. Pearson Correlation test was used for correlation analysis. The level of significance for all tests is α = 0.05. Results: In the findings obtained from the study, it is observed that the mean scores of the scale scores of the participants according to gender, nutritional feelings, emotional eating scale and perfectionism scale do not differ significantly according to gender (p